Visiting Albert and Rose Watkins And Friends in Southern California - Watkins, Howard::::::::: (1983)
Batsheva Eitan, Yuki Hayashi, Adam Watkins, Rose Watkins, George Hayashi, Albert Watkins holding Robin Watkins